Pengaruh Komunikasi Organisasi Pimpinan terhadap Kinerja Karyawan pada Mutia Catering Medan - Muhammad Farhan Fathurrahman; Erwan Efendi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine the influence of managerial organizational communication on employee performance at Mutia Catering Medan. Organizational communication is one of the key factors in improving employee work effectiveness, particularly through vertical and horizontal communication between leaders and subordinates. Communication plays a crucial role in the operation of an organization and ensures that organizational tasks run smoothly. This research employs a quantitative approach with a descriptive research design. Data collection was conducted by distributing questionnaires to 10 employees selected through purposive sampling. The research instruments were tested for validity using the t-test at a 5% significance level, and all items related to the variables of managerial organizational communication (X) and employee performance (Y) were found to be valid. The results of this study show that managerial organizational communication—encompassing openness, empathy, support, a positive attitude, and equality—has a positive relationship with good employee performance. This study indicates that effective communication from leadership plays an important role in fostering a productive and collaborative work environment at Mutia Catering Medan.